Prevalence of vegan/vegetarian diet and eating behavior among Saudi adults and its correlation with body mass index: A cross-sectional study - Mohammed AL-Mohaithef (Frontiers in Nutrition, 2022)
BackgroundGlobalization has steered the spread of vegetarianism around the world. Vegetarianism has achieved increased acceptance by different populations.ObjectiveThe present study aims to assess vegetarian diet, and eating behavior prevalence among Saudi adults and their association with demographics and body mass index.MethodA cross-sectional study conducted on 1,143 Saudi adults [418 (36.6%) males and 725 (63.4%) females]. An online survey questionnaire containing questions on demographics, type of diet, eating behavior and physical activity was provided to participants for self-administration. Statistical analysis was performed to associate demographic and eating behavior variables with the type of diet using Pearson's Chi-square test and Spearman's partial correlation test was used to correlate BMI and eating behavior.ResultsPrevalence of veganism was 4.7% (n = 54/1,143) and vegetarianism was 7.8% (89/1,143). A significantly higher prevalence of vegan diet was observed in females than males (79.6% vs. 20.4%, p < 0.0001). A significantly higher proportion of participants on vegetarian diet selected “Always” as response for eating breakfast, vegetables and fruits as well as for eating or drinking dairy foods, and for eating canned food than participants on non-vegetarian diet (p < 0.0001). A significantly higher proportion of participants on vegan diet selected ‘Never' for eating fast-food and fried food as well as for drinking fizzy or soft drinks (p < 0.0001). A positive moderate correlation was found between BMI and eating fast-food and fried food [r(1, 140) = 0.529, p < 0.0001], drinking fizzy or soft drinks with meals [r(1, 140) = 0.495, p = 0.001], and eating canned food [r(1, 140) = 0.510, p < 0.0001].ConclusionOur study shows that vegan and vegetarian diet have gained access into the lifestyle of Saudi adults with a prevalence of 4.7 and 7.8%, respectively. Participants on vegetarian diet showed better lifestyle like higher physical activity level, higher consumption of fruits, vegetables, dairy products and low intake of fast-foods and fizzy beverages.